Village Fund Management in Community Empowerment: Study in Bendan Village, Banyudono Subdistrict, Boyolali Regency - Aprilliansyah, Dheny; Purwanto , Danang; Parahita, Bagas Narendra (Universitas Wiralodra, 2024)
This research aims to describe the implementation of village fund management in community empowerment and to determine several factors that support and hinder the process of managing village funds in community empowerment. This research uses a qualitative method with a case study approach. The research was conducted in Bendan Village, Banyudono District, Boyolali Regency and data collection was collected using in-depth observation and interviews. The results of the research show that the management of village funds carried out by the Bendan Village government has gone very well and has been adapted to priority needs in the community, such as the post-pandemic food security program, the PKK development program for mothers, and the BUMDes formation program to manage various assets and potential. Owned by Bendan Village. The management of village funds for non-physical community empowerment is carried out in a more varied way by using the village's potential to encourage the community to be more independent in producing products such as food security programs in fish cultivation, goat cultivation, and grape cultivation. Supporting factors for managing village funds in empowering communities in Bendan Village are the timely disbursement of village funds, government policies, and the condition of local natural resources. Meanwhile, the inhibiting factors are the lack of community resources in Bendan Village and the village government's weak process of empowering the community.